The Third Rome, 1922-43 - Kallis, Aristotle. author. aut Link
XIV, 324 p.
Keywords: What kind of city was the Fascist 'third Rome'? Imagined and real, rooted in the past and announcing a new, 'revolutionary' future, Fascist Rome was imagined both as the ideal city and as the sacred centre of a universal political religion. Kallis explores this through a journey across the sites, monuments, and buildings of the fascist capital.